(untitled) (Journal of Parents and Teachers, 2024)
The article is based on a true story, where a young girl writes in her letter to the Three Wise Men asking for all the toys from El Corte Inglés, due to all the advertisements she had seen in the months leading up to Christmas. It also presents real data on the amount spent by toy companies on advertising, highlighting the importance of investing in it.